In Situ Generated DBU⋅HF Acts as a Fluorinating Agent in a Hexafluoroisobutylation Tandem Reaction: An Effective Route to 5, 5, 5, 5', 5', 5'‐Hexafluoroleucine. Issue 10 (22nd November 2022) - Naulet, Guillaume; Delamare, Aline; Guichard, Gilles; Compain, Guillaume
Abstract: We report the direct incorporation of the hexafluoroisobutyl group on a chiral glycine Schiff base complex mediated by 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU). The fluoroalkylation involves 2‐(bromomethyl)‐1, 1, 1, 3, 3, 3‐hexafluoropropane reagent, which generates in situ hexafluoroisobutylene (HFIB), and reacts then with the enolate through a tandem allylic shift/hydrofluorination process. We showed that the use of neutral organic base DBU generates in situ an original DBU⋅HF salt, which preserves the fluoride nucleophilicity and acts as a fluorinating agent. This fluoride salt promotes the hydrofluorination of the pentafluorinated alkene overcoming the usual fluoride β‐elimination observed with α‐CF3 ‐vinyl reagents. With alkali metal bases, by contrast, the hydrofluorination is disfavored and the pentafluorinated alkene intermediate is obtained predominantly. This study highlights the critical role of the fluoride counter ion to preserve its nucleophilicity. The protocol is amenable to multidecagram scale synthesis of enantiopure ( S )‐ and ( R )‐5, 5, 5, 5', 5', 5'‐hexafluoroleucine and their N‐Fmoc or N‐Boc derivatives in good overall yield. Abstract : A stereoselective synthesis of both ( S )‐ and ( R )‐5, 5, 5, 5', 5', 5'‐hexafluoroleucine mediated by DBU through a cascade reaction is reported. The pivotal role of the organic base to preserve the nucleophilicity of the fluoride released during the process is shown. The direct incorporation of the hexafluorinated side chain allows for the facile preparation of the free and suitably protected fluorinated amino acids on a multidecagram scale.